Sudden cardiac arrest in hypertrophic cardiomyopathy with dynamic cavity obstruction: The case for a decatecholaminisation strategy. (February 2018) - Balan, Cosmin; Wong, Adrian View-Kim
Catecholamines are entrenched in the management of shock states. A paradigm shift has pervaded the critical care arena in recent years acknowledging their propensity to cause harm and fuel a 'death-spiral'. We present the case of a 21-year-old male following a witnessed out-of-hospital cardiac arrest who received high-quality cardiopulmonary resuscitation and standard advanced life support for refractory ventricular fibrillation until return of spontaneous circulation after 70 min. Early post-admission echocardiography revealed severe diffuse sub-basal left ventricular hypertrophy with dynamic mid-cavity obstruction and akinetic apical pouching. Within this context, a decatecholaminised strategy comprising a beta-blocker was used to augment the left ventricular end-diastolic volume and attain cardiovascular stability.